Fraction of all hospital admissions and deaths attributable to malnutrition among children in rural Kenya. - Bejon, P; Mohammed, S; Mwangi, I; Atkinson, S; Osier, F; Peshu, N; Newton, C; Maitland, K; Berkley, J (2008)
BACKGROUND: Malnutrition is common in the developing world and associated with disease and mortality. Because malnutrition frequently occurs among children in the community as well as those with acute illness, and because anthropometric indicators of nutritional status are continuous variables that preclude a single definition of malnutrition, malnutrition-attributable fractions of admissions and deaths cannot be calculated by simply enumerating individual children. OBJECTIVE: We determined the malnutrition-attributable fractions among children admitted to a rural district hospital in Kenya, among inpatient deaths and among children with the major causes of severe disease. DESIGN: We analyzed data from children between 6 and 60 mo of age, comprising 13,307 admissions, 674 deaths, 3068 admissions with severe disease, and 562 community controls by logistic regression, using anthropometric z scores as the independent variable and admission or death as the outcome, to calculate the probability of admission as a result of "true malnutrition" for individual cases. Probabilities were averaged to calculate attributable fractions. RESULTS: Z scores < -3 were insensitive for malnutrition-attributable deaths and admissions, and no single threshold was both specific and sensitive. The overall malnutrition-attributable fraction for in-hospital deaths was 51% (95% CI: 42%, 61%) with midupper arm circumference. Similar malnutrition-attributable fractions were seen for the major causes of severe disease (severe malaria, gastroenteritis, lower respiratory tract infection, HIV, and invasive bacterial disease). CONCLUSIONS: Despite global improvements, malnutrition still underlies half of the inpatient morbidity and mortality rates among children in rural Kenya. This contribution is underestimated by using conventional clinical definitions of severe malnutrition.